2009
DOI: 10.1016/j.nbd.2008.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in remote memory stabilization precede hippocampal synaptic and cognitive failures in 5XFAD Alzheimer mouse model

Abstract: Although animal models of Alzheimer's disease (AD) recapitulate β-amyloid-dependent hippocampal synaptic and cognitive dysfunctions, it is poorly understood how cortex-dependent remote memory stabilization following initial hippocampal coding is affected. Here, we systematically analyzed biophysical and behavioral phenotypes, including remote memory functions, of 5XFAD APP/PS1 transgenic mice containing five familial AD mutations. We found that 5XFAD mice show hippocampal dysfunctions as observed by reduced le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
225
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(264 citation statements)
references
References 52 publications
36
225
1
2
Order By: Relevance
“…We also tested PPF, which represents a short-term form of synaptic plasticity reflecting presynaptic function. Consistent with the previous report that PPF was not affected in 5XFAD mice (Kimura and Ohno, 2009), we found that the ratio of paired pulse was similar when comparing nontransgenic control, vehicle-and 7,8-DHF-treated 5XFAD (Figure 5b). Then we tested the basal synaptic transmission at CA1 synapses by measuring the input/ output (I/O) curves.…”
Section: Chronic Oral Administration Of 78-dhf Restores Synaptic Plasupporting
confidence: 92%
See 1 more Smart Citation
“…We also tested PPF, which represents a short-term form of synaptic plasticity reflecting presynaptic function. Consistent with the previous report that PPF was not affected in 5XFAD mice (Kimura and Ohno, 2009), we found that the ratio of paired pulse was similar when comparing nontransgenic control, vehicle-and 7,8-DHF-treated 5XFAD (Figure 5b). Then we tested the basal synaptic transmission at CA1 synapses by measuring the input/ output (I/O) curves.…”
Section: Chronic Oral Administration Of 78-dhf Restores Synaptic Plasupporting
confidence: 92%
“…5XFAD mice show significantly impaired LTP at the Schaffer collateral-CA1 pathways compared with non-transgenic mice (Kimura and Ohno, 2009). We examined whether chronic oral 7,8-DHF treatment can rescue LTP deficit observed in hippocampal slices from 5-month-old 5XFAD mice.…”
Section: Chronic Oral Administration Of 78-dhf Restores Synaptic Plamentioning
confidence: 99%
“…5XFAD mice start to develop visible amyloid deposition as early as 2 months of age consistent with their dramatically accelerated Ab42 production because of a combination of the multiple FAD mutations, thus representing an early onset and aggressive amyloid mouse model . At 4-6 months of age, 5XFAD mice start to show impairments in hippocampus-dependent learning and memory as tested by the Y-maze, Morris water maze, and contextual or trace fear conditioning paradigms (Kimura and Ohno, 2009;Oakley et al, 2006;Ohno et al, 2006). These behavioral deficits are observed concomitant with the onset of hippocampal CA1 synaptic dysfunctions such as reduced basal transmission and long-term potentiation (LTP: a synaptic plasticity model for learning and memory) (Kimura and Ohno, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…At 4-6 months of age, 5XFAD mice start to show impairments in hippocampus-dependent learning and memory as tested by the Y-maze, Morris water maze, and contextual or trace fear conditioning paradigms (Kimura and Ohno, 2009;Oakley et al, 2006;Ohno et al, 2006). These behavioral deficits are observed concomitant with the onset of hippocampal CA1 synaptic dysfunctions such as reduced basal transmission and long-term potentiation (LTP: a synaptic plasticity model for learning and memory) (Kimura and Ohno, 2009). Furthermore, 5XFAD mice begin to exhibit elevations in expression levels of the b-secretase (b-site APP cleaving enzyme 1: BACE1), which is responsible for initiating the production of Ab, at 6-9 months of age (Devi and Ohno, 2010b;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007), as observed in sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…the ability to calculate, and use common objects and tools. 9 The current symptomatic treatment of patients with mild to moderate AD is based on drugs such as donepezil, rivastigmine, galantamine and memantine which are associated with side effects. 10 These drugs may help keep symptoms from getting worse for a limited time.…”
Section: Introductionmentioning
confidence: 99%